Min A‘lāmi Indūnīsīya: al-Shaykh Yūsuf al-Makassarī (1626-1699) - Lubis, Nabilah (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 1994)
Shaykh Yusuf Makassar, a Sufi, a great alim and statesman who think about and fight for the fate of his nation. He was born in the kingdom of Gowa, Makassar, South Sulawesi Province. Since childhood, he was raised in the court of Sultan Alauddin and he gained an education in religion as well as memorizing the Qur'an at a young age. He was studying in Aceh, Yemen, Mecca and Syria. Shaykh Yusuf obtain allegiance almost the entire congregation of the teachers directly. Once the knowledge was enough, he soon returned to introduce it and preach in his homeland, Gowa.DOI: 10.15408/sdi.v1i3.852